Intermediate stable states in substance use. (June 2022) - Epskamp, Sacha; van der Maas, Han L.J.; Peterson, Roseann E.; van Loo, Hanna M.; Aggen, Steven H.; Kendler, Kenneth S.
Highlights: There is evidence for stable moderate use of alcohol and cannabis throughout the lifespan and even after a dependency diagnosis. There is less evidence for stable moderate tobacco usage. Achieving three stable states (zero-use, moderate use and heavy use) should be the target in complex systems modeling of substance use. Abstract: Many people across the world use potentially addictive legal and illegal substances, but evidence suggests that not all use leads to heavy use and dependence, as some substances are used moderately for long periods of time. Here, we empirically examine, the stability of and transitions between three substance use states: zero-use, moderate use, and heavy use. We investigate two large datasets from the US and the Netherlands on yearly usage and change of alcohol, nicotine, and cannabis. Results, which we make available through an extensive interactive tool, suggests that there are stable moderate use states, even after meeting criteria for a positive diagnosis of substance abuse or dependency, for both alcohol and cannabis use. Moderate use of tobacco, however, was rare. We discuss implications of recognizing three states rather than two states as a modeling target, in which the moderate use state can both act as an intervention target or as a gateway between zero use and heavy use.